The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-3180.2009.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Orobanche and Phelipanche–host plant interactions and developing resistance

Abstract: Summary Orobanche and Phelipanche spp. (broomrapes) are parasitic plants that can be responsible for devastating losses in several important crops. The development of resistant cultivars is one of the key strategies in the fight against this pest. However, the nature of resistance is complex and the basis of the interaction between the host and the parasite is still largely unknown. Despite the progress achieved during the last century through breeding programmes, sources of resistance are often scarce (e.g. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 89 publications
(148 reference statements)
1
44
0
Order By: Relevance
“…Quantitative trait loci (QTL) analyses showed that, in addition to the major gene Or 5 , resistance to race E has also a quantitative component determined by four QTLs with minor effects, in some cases non-race specific and mainly associated with the number of broomrape stalks per plant (Pérez-Vich et al, 2004). The existence of this polygenic component in race E resistance is supported by histological observations and gene expression studies that demonstrated that several mechanisms such as reduced stimulation of broomrape seed germination or rapid necrosis at early stages of parasite development are involved in resistance to this broomrape race (Labrouse et al, 2001;Pérez de Luque et al, 2009). In contrast to race E, molecular studies concluded that recessive resistance to race F in sunflower line P-96 was determined by six QTL, some of which were non-race specific and stable over environments (Pérez-Vich et al, 2004).…”
Section: Characterization Of Resistancementioning
confidence: 97%
“…Quantitative trait loci (QTL) analyses showed that, in addition to the major gene Or 5 , resistance to race E has also a quantitative component determined by four QTLs with minor effects, in some cases non-race specific and mainly associated with the number of broomrape stalks per plant (Pérez-Vich et al, 2004). The existence of this polygenic component in race E resistance is supported by histological observations and gene expression studies that demonstrated that several mechanisms such as reduced stimulation of broomrape seed germination or rapid necrosis at early stages of parasite development are involved in resistance to this broomrape race (Labrouse et al, 2001;Pérez de Luque et al, 2009). In contrast to race E, molecular studies concluded that recessive resistance to race F in sunflower line P-96 was determined by six QTL, some of which were non-race specific and stable over environments (Pérez-Vich et al, 2004).…”
Section: Characterization Of Resistancementioning
confidence: 97%
“…Only moderate to low levels of incomplete resistance of complex inheritance against O. crenata have been identified in legumes Pérez-de-Luque et al 2009;Sillero et al 2010) making selection more difficult and slowing down the breeding process. Resistance to broomrape appears to have multiple components and to be based on a chain of escape and resistance mechanisms that either act alone or in combination and at different stages of the infection process (Rubiales 2003).…”
Section: Sources Of Resistancementioning
confidence: 99%
“…The integration of information obtained from QTL analysis with gene and protein expression analysis currently performed in pea or in the model plant M. truncatula in response to O. crenata infection (Castillejo et al 2004(Castillejo et al , 2009(Castillejo et al , 2012Die et al 2007;Dita et al 2009) can shortcut conventional breeding or marker-assisted selection in identifying candidate genes. Also, sequence information obtained from different parasitic plant species (Westwood et al 2012) will help in understanding parasite virulence and host resistance mechanisms.…”
Section: Potential Applications Of Biotechnology In Broomrape Resistamentioning
confidence: 99%
“…Only incomplete resistance to O. crenata was found in other grain legumes like faba bean that has been successfully accumulated by breeding, allowing the release of resistant cultivars (Pérez-De-Luque et al 2009). A similar effort in pea breeding for broomrape resistance has been started only recently.…”
Section: Crenate Broomrape (Orobanche Crenata Forssk)mentioning
confidence: 99%